2008
DOI: 10.1093/humrep/den325
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial comparing laparoscopic ovarian diathermy with clomiphene citrate as a first-line method of ovulation induction in women with polycystic ovary syndrome

Abstract: LOD is not superior to CC as a first-line method of OI in women with PCOS. The trial is registered with ClinicalTrials.gov with an identifier number NCT00220545.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(37 citation statements)
references
References 30 publications
1
35
0
1
Order By: Relevance
“…15 Miscarriage rate following LOD in our series was similar to the previously reported figures. 25,26 Of the five multiple pregnancies reported in our cohort none occurred after spontaneous conception and their frequency was similar to what was previously described (0% -10%). 15 Laparoscopic ovarian diathermy is not a curative treatment for PCOS, but is associated with long-term beneficial effects.…”
Section: Discussionsupporting
confidence: 90%
“…15 Miscarriage rate following LOD in our series was similar to the previously reported figures. 25,26 Of the five multiple pregnancies reported in our cohort none occurred after spontaneous conception and their frequency was similar to what was previously described (0% -10%). 15 Laparoscopic ovarian diathermy is not a curative treatment for PCOS, but is associated with long-term beneficial effects.…”
Section: Discussionsupporting
confidence: 90%
“…In IVM, immature oocytes are collected without exposing them to gonadotropin stimulation (9). Compared with IVF, IVM is simpler, less costly, and more importantly avoids the risk of OHSS.…”
mentioning
confidence: 99%
“…Laparoscopic ovarian drilling improves ovulation rates likely through destruction of theca cells in the ovary that produce androgens resulting in increased FSH levels and reduced LH levels conducive to normal follicular development. As a first line treatment, randomised trials have shown similar results for ovulation, conception and live birth rates when compared with up to 6 cycles of clomiphene [42] and has a likely ongoing success rate without the risk of multiple pregnancy from clomiphene.…”
Section: Laparoscopic Ovarian Drillingmentioning
confidence: 93%